Taxonomic review of Eurasian Paradelia Ringdahl (Diptera: Anthomyiidae)with descriptions of two new species - Michelsen, Verner (Zootaxa, 2007)
Paradelia Ringdahl is a modest-sized, anthomyiid genus found in cool-temperate to arctic situations in northern and elevated parts of Eurasia and North America. A high percentage of the known Eurasian species are more widespread, Holarctic in distribution. The monophyly of the genus is well supported, though it is less easy to place unambiguously in a phylogeny. Most species are rarely collected and there exists no substantial information on the biology of immatures and adults even for the only common species, P. intersecta (Meigen). The Eurasian species are reviewed with illustrateddescriptions and an identification key to males and females. Two new species are described: P. uleforsi sp. nov. from Europe and Mongolia and P. manni sp. nov. from northern Pakistan, making a total of 15 named, recognized species in Eurasia. Known distributions are substantially widened for several species.